PENGGUNAAN NUN TAUKID TSAQILAH DALAM ALQURAN: WUJUD DAN FUNGSINYA - LAILY MAZIYAH (Prosiding Konferensi Nasional Bahasa Arab, 2016)
The main objective of this study is describing the use of nun taukid tsaqilah in the Quran. This objective of this study is thus to describe and analyzing (1) the forms of verses that use nun taukid tsaqilah in the Quran, (2) the addressee of the emphatics verses that uses nun taukid tsaqilah in the Quran, and (3) the functions of the emphatics verses that use nun taukid tsaqilah in the Quran. The research is qualitative in nature that uses analysis content. The main instrument in this research is the researcher as a human instrument. The data of this study were the Quranic verses that contained mudhari’ mustaqbal verbs and nahyi verbs that followed by nun taukid tsaqilah. The choice of the verses was done purposively. The data analysis model used in this research was content analysis model by Krippendorf that was adopted by Ainin. The study shows that the emphatics in the Quran can be classified into five categories, they are: assertive acts, directive acts, commisive acts, expressive acts, and declarative acts. Key words: nun taukid tsaqilah, wujud, fungsi.